Non-performing loan insulation factors / Muhammad Zafri Zambari - Zambari, Muhammad Zafri (2022)
The purpose of this study was to examine the impact of non-performing loans on commercial banks in Malaysia. Bank size, bank profitability, cost efficiency, unemployment rate, and interest rate on non-performing loans were employed in the study. The databases and annual reports of the sampled firms were used to gather data for this study. There were three conventional banks that were listed on Bursa Malaysia between 2011 and 2020 that were utilised in this study. In this study, panel data was utilised to analyse the acquired data. Autodescriptive analysis, correlation analysis, and regression analysis were used in this study. As a consequence of this discovery, the theory put out by Berger and DeYoung (1992) that poor management in financial institutions leads to subpar loans and hence an increase in nonperforming loans, is now even more firmly backed up.